Stagecoach Robberies in California : a Complete Record, 1856-1913. - Wilson, R. Michael (McFarland & Company, Inc., Publishers, 2014)
California was the mining center of the West for half a century. Wherever precious minerals were found, road agents appeared to ""mine the roads"" of treasure being shipped out and payrolls being shipped in. The first recorded robbery of a stagecoach occurred in 1856, and the last in 1913. Over that period there were 458 stagecoach robberies, many with special characteristics such as a claim the robbers were Confederate soldiers, a murder, a gun battle, or a thrilling pursuit and capture. Surprisingly, there were many robberies in which the perpetrator remained unknown or in which was so littl.